Diaquabis{1-[(1H-benzimidazol-2-yl)methyl]-1H-imidazole-κN (3)}dichloridocadmium hexahydrate - Xie, Xin-Nian (International Union of Crystallography, 2012)
In the title complex, [CdCl(2)(C(11)H(10)N(4))(2)(H(2)O)(2)]·6H(2)O, the Cd(II) atom is located on a twofold rotation axis and is coordinated by two N atoms from two 1-[(1H-benzimidazol-2-yl)methyl]-1H-imidazole ligands and two water O atoms in equatorial positions and by two Cl atoms in axial positions, leading to an elongated octahedral environment. The two coordinating and two of the lattice water molecules are also located on twofold rotation axes. In the crystal, complex molecules and solvent water molecules are linked through a complex intermolecular N—H⋯O, O—H⋯N, O—H⋯O and O—H⋯Cl hydrogen-bonding scheme into a three-dimensional network.